GE_GERICHTE P/15776/2017 vom 26. Juli 2022 - GE Cour de justice (2022)
PRINCIPE DE LA CÉLÉRITÉ;CLASSEMENT DE LA PROCÉDURE;ESCROQUERIE;ASTUCE;BLANCHIMENT D'ARGENT | Cst.29.al1; CPP.5; CPP.319.al1.letd; CPP.319.al1.letc; CPP.8.al3; CPP.319.al1.letb; CP.146; CP.138; CP.305bis